Evolving relations between agriculture and forest in Viengkham District, Luang Prabang Province - Castella, J.C.; Thephavanh, M.; Vongkhamsao, V.; Mouaxeng-Cha, K.; Phonphakdy, S.; Fitriana, Y.R.; Kongay, K.; Phaipasith, S.; Ferrand, J.; Manivanh, V.; Pfund, J.L. (2011)
The paper investigates the changes in management and trade of non timber forest products (NTFP) in northern uplands of Laos and how they are related to agricultural production from both landscape and livelihoods perspectives. Surveys were conducted in Luang Prabang province with multiple groups of stakeholders (e.g. villagers, traders, officials from different administrations) to compare the value chains of agricultural and forest products and assess their interactions. Analysis of remote sensing data and literature review complemented field investigations to describe the historical changes in land use and in the management of NTFP and agricultural commodities. The study revealed how forest and agriculture products are complementary from both an economic perspective: i.e. how they complement each other in household economics and traders businesses; and an ecological perspective: i.e. how they complement each other at the landscape level. At the landscape level, the complex mosaics of agriculture and forest patches are key assets in term of resilience of the overall system in the face of unpredictable natural events (e.g. floods, droughts, fires). The main lesson is that the on-going segregation of agricultural and forest spaces tend to increase economical and ecological vulnerability by decreasing diversity in landscapes and livelihood systems. The on-going trend of specialization of farming activities as a result of the shifting cultivation eradication policy should be buffered in such a way that multiple livelihood systems and economic development pathways can be maintained. The loss in the resilience of the socio-ecological system due to simplification of the natural landscape should be compensated by improved mechanisms for landscape governance.